Collaborative Governance and Effectiveness of Vocational Training and Graduate Job Placement: An Ansell and Gash Perspective - Darmawansyah; Nurliah Nurdin; Muhammad Taufiq; R Luki Karunia (Jurnal Ketenagakerjaan, 2026)
Vocational training in Indonesia, specifically at the Vocational Training and Productivity Center (VPTC) in Samarinda and Makassar, continues to struggle with suboptimal graduate employability. This research identifies a critical disconnect between institutional training and industrial demand, rooted in fragmented multi-stakeholder collaboration. Using the Ansell and Gash (2008) Collaborative Governance framework, this study analyzes the governance dynamics hindering effective job placement. Employing a qualitative multi-site case study approach—comprising document analysis, Focus Group Discussions (FGD), and field observations—the findings reveal a "cycle of collaborative dysfunction." The starting conditions are characterized by structural power imbalances, while the collaborative process remains largely ceremonial, failing to foster the strategic trust and shared understanding necessary for curriculum co-creation. Consequently, intermediate outcomes, such as synchronized industry-needs assessment and robust placement networks, remain unachieved. This study underscores the urgent need for institutional reform, including the formalization of Standard Operating Procedures (SOPs) for industry partnerships and the professionalization of Public Employment Services (PES). These measures are vital to transitioning from administrative compliance to a demand-driven vocational ecosystem.